Pattern of Sleep in Infants and Toddlers Visiting at a Teaching Hospital in Lalitpur - Shrestha, D; Dhakal, AK; Shakya, A; Shah, SC; Shakya, H; Mehata, S; Sadeh, A (Journal of Nepal Paediatric Society, 2015)
Introduction: Sleep is an integral part in a child’s health and development. During different stages of development, there are aberrations in normal physiology of sleep which make children more susceptible to various types of sleep problems. This study was conducted to identify sleep pattern and sleep problems in Nepalese children using Nepali translation of Brief Infant Sleep Questionnaire (BISQ) screening tool. Materials and Methods: This was a descriptive cross-sectional study. Data were collected from parents of children aged 6 to 36 months attending paediatric out-patient clinic for general health check-up from July 2013 to December 2013. Nepali translation of the BISQ was used as a screening tool for sleep problems in this study. Results: The study included 553 children (52.4% boys). Mothers completed the questionnaire in 92% of children. Mean total duration of sleep in 24 hours was 11.7 ±1.7 hours. Respondents reported sleep problem in 16.9% of children whereas 20.3% of children had sleep problems according to BISQ criteria. As per this criteria, 2.7% of children had total sleep duration less than 9 hours, 5.9% of children had total night awakening duration of more than one hour, 13.9% of children had night waking >3 times. These BISQ sleep parameters differed significantly in children with and without sleep problems (p<0.001). In addition, children with sleep problem took longer time to sleep than children without sleep problems (p<0.001). Conclusion: Sleep problems are common in Nepalese infants and toddlers according to the BISQ. Screening for sleep problems is highly recommended during health care visits given the prevalence of sleep problems identified by this study to reduce their potential adverse impact. J Nepal Paediatr Soc 2015;35(1):24-30